Saint Vincent trade with Barbados expanded - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Green bananas and plantains from Saint Vincent and the Grenadines have entered the market in Barbados after a nearly 3-year absence. Barbados had placed a ban on certain Saint Vincent produce owing to the pink mealybug pest.